Decontamination of Mercury from Mined Soil using Magnetite Functionalized Quaternary Ammonium Silica (Fe3O4/SAK) - Ngatijo Ngatijo; Defia Indah Permatasari; Faizar Farid; Restina Bemis; Heriyanti Heriyanti; Rahmat Basuki; Yudha Gusti Wibowo (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
Artisanal small-scale gold mining (ASCGM) has caused mercury contamination. However, efforts to decontaminate mercury from the ex-mining soils are still rare. This study aims to synthesize quaternary ammonium silica functionalized magnetite (Fe3O4/SAK) as a low price, highly available, and quickly separated adsorbent for mercury decontamination from ex-mining soils samples. The synthesis of Fe3O4/SAK and the mercury decontamination process was carried out by the co-precipitation and batch type reactor procedure, respectively. The Fourier Transform-Infra Red (FT-IR) characterization of synthesized Fe3O4/SAK informed the appearance of siloxane, silanol, methyl, methylene, and Fe-O functional groups. Crystal analysis by X-Ray Diffraction (XRD) showed that the typical peaks of SiO2 and Fe3O4 were emerged at 2θ 22.8˚ and 35.52˚, respectively. Morphological studies and elemental analysis using Scanning Electron Microscopy-Energy Dispersive X-Ray (SEM-EDX) indicated the successful functionalization Fe3O4 by SAK in the transformation of surface morphology and composition of the main elements, namely C, O, Si, and Fe. The results of characterization using Surface Area Analyzer (SAA) showed that the surface area and pore diameters were 224.98 m2/g and 36.149-38.70 Å, respectively. The optimum results for adsorbing Hg22+ metal ions were obtained at pH 4.0, and the adsorbent mass was 0.1 g. The Fe3O4/SAK has been proven to be an easily separable adsorbent after the mercury decontamination process in ex-mining soil samples with an adsorption efficiency of 43.36% (0.722 mg/g).